Voice of Empowerment: Debunking Gendered Language in Emma Watson’s Advocacy - Rosyidah, Nur; Suhandoko, Suhandoko; Syuhra, Marsha Aqillah Putri; Rochmah, Maulidya (Universitas Sanata Dharma, 2024)
For nearly five decades, Robin Lakoff’s women’s language features have been well examined. These features such as hedges, intensifiers, and rising intonation have traditionally positioned women as powerless language users due to their less-assertive nature. However, few have highlighted how these features can serve as rhetorical strategies that can effectively utilized to argue confidently without appearing overly assertive, in line with social expectations. This study examines women’s language features used by Emma Watson at the HeForShe Campaign 2014. By using a descriptive qualitative method, we collected data from Emma’s speech to identify the features of the women’s language that she used to address gender equality issues. The study found six of Lakoff’s (1975) women’s language features, with lexical hedges being the most frequently used to represent politeness and caution in speaking as well as expressing respect for the interlocutor. Notably, tag questions, precise color terms, hypercorrect grammar, and avoiding strong swear words were not found, likely due to their irrelevance to the feminism-focused topic in the campaign. Instead of highlighting the perceived weaknesses of women’s language, this study emphasizes that women’s language can be a means to empower women’s voices. Emma effectively and persuasively delivered her campaign by using her mastery of language, storytelling techniques, and rhetoric to engage the audience. Overall, Emma strategically utilized women’s language to demonstrate her linguistic capability and even persuade the audience effectively rather than showing the weakness of women’s language as commonly perceived by previous studies.